PENERAPAN BANTUAN HUKUM DALAM PROSES PENYIDIKAN DENGAN PRINSIP ACCUSATOIR - Muhammad Rusli Arafat (Faculty of Law, Universitas Pekalongan, 2019)
Investigation of criminal case through the criminal justice system must to base on the appropriate processes and procedure that can be accounted. One of the important procedures to investigation is the right to get legal protection. Legal protection is one of the fundamental rights that every human being possesses, one form of legal protection is right to obtain legal aid in every steps of investigation process. The legal aid has an important meaning for someone who dealing with legal issues. This research is discussed about application of legal aid in the process of police investigation. This research also specializes in the approach using the rule of national law (legislation) to be able to know the application of legal aid with the principle of accusatoir. The result of this research is Legal aid can reduce the number of violence in the process of investigation of suspects by the police (investigation) in order to protect the human rights of the suspect, the role of legal aid is needed, the number of investigation of suspects not accompanied by advocate it cause torture of the suspect, because the investigator considers the suspect to be an object of inspection instead of placing the suspect as the subject of the investigation.Keywords: The criminal justice system, Investigation, legal aid, accusatoir principle